The User Requirement Based Competitive Price Model for Spectrum Sharing in Cognitive Radio Networks. (25th November 2013) - Ye, Fang; Li, Yibing; Yang, Rui; Sun, Zhiguo
We analyze the competitive price game model for spectrum sharing in cognitive radio networks with multiple primary users and secondary users and propose a user requirement based competitive price game model for the calculation of the shared spectrum size of cognitive user in Bertrand game. The communication requirement of the cognitive user is quantified into different requirement levels. With the application of spectrum requirement factor, cognitive user can adjust the demanded shared spectrum size according to self-requirement level and the shared spectrum price provided by licensed users. It can avoid the waste of spectrum resource caused by the overdistribution of spectrum to the cognitive user with low communication requirement. Simulation results show that the occupied spectrum of cognitive user can be adjusted with the variation of requirement levels, and the licensed users can achieve better profit performance with consideration of requirement of cognitive user by adjustment of the shared spectrum price proposed spectrum sharing model.